2018
DOI: 10.1242/jeb.186270
|View full text |Cite
|
Sign up to set email alerts
|

Gliding for a free lunch: biomechanics of foraging flight in common swifts (Apus apus)

Abstract: Although the biomechanics of animal flight have been well studied in laboratory apparatus such as wind tunnels for many years, the applicability of these data to natural flight behaviour has been examined in few instances and mostly in the context of long-distance migration. Here, we used rotational stereo-videography to record the free-flight trajectories of foraging common swifts. We found that, despite their exquisite manoeuvring capabilities, the swifts only rarely performed high-acceleration turns. More s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…We showed that Turkey vultures respond to a fundamental environmental gradient that could impact their flight performance, the decrease of air density at high elevation by increasing their flight speed and adjust their flight speed to optimize their gliding flight. The tool that we used was developed for field studies of biomechanics [13,14,25,38], but this study also demonstrates that tools from the biomechanics toolchest can be successfully applied to ecological questions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We showed that Turkey vultures respond to a fundamental environmental gradient that could impact their flight performance, the decrease of air density at high elevation by increasing their flight speed and adjust their flight speed to optimize their gliding flight. The tool that we used was developed for field studies of biomechanics [13,14,25,38], but this study also demonstrates that tools from the biomechanics toolchest can be successfully applied to ecological questions.…”
Section: Discussionmentioning
confidence: 99%
“…airspeed adjusted for air density), and 𝑘 2 is the induced power coefficient. See Hedrick et al (2018) for further details on this calculation. Literature values of 0.456 m 2 and 2.18 kg [31] were used for 𝑆 (wing area) and 𝑚 (body mass), respectively.…”
Section: Glide Polar Calculationmentioning
confidence: 99%
“…This approach is similar in principle to that used to estimate local wind speed from the drift in the ground reference frame position of circling vultures (Weinzierl et al, 2016), and shares the important assumption that airspeed is independent of wind direction. However, birds are theoretically expected and empirically known to vary airspeed with wind speed when flying in order to reach a destination efficiently (Hedrick et al, 2018; Shamoun-Baranes et al, 2007). Whether this is the case for shorebird flocks (making shorter flocks around the stopover point) is unknown, so we did not attempt to model this possible effect.…”
Section: Methodsmentioning
confidence: 99%
“…1c). COT is calculated for a given distance and so could be considered in the inertial frame [31]; however, in environmental harvesting strategies, it is the airspeed in relation to the wind which should be optimized [30]. This study considers the wind vectors in the air and inertial frame as side and crosswinds, respectively.…”
Section: B Cost Of Transport Theorymentioning
confidence: 99%